2014
DOI: 10.1590/0004-2730000003393
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable factors of vitamin D status among a Brazilian osteoporotic population attended a public outpatient clinic

Abstract: In a cross-sectional study, 363 community-dwelling patients who sought specialized medical care were evaluated between autumn and spring in São Paulo, Brazil. Serum levels of 25(OH)D and parathormone (PTH), biochemical and anthropometric measurements, and bone density scans were obtained. The group was assessed using two questionnaires: one questionnaire covered lifestyle and dietary habits, skin phototype, sun exposure, medical conditions, and levels of vitamin D supplementation (cholecalciferol); the other q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The present crosssectional study used the baseline data from all these women as they entered the study protocols, which were conducted by the same professionals and utilized the same methodology for measurement of antrhopometric and body composition parameteres. The selection criteria for choosing study participants are described in details in the publications resulting from these three studies (9)(10)(11). For further analysis, these women were divided into two groups: 430 that were undergoing treatment for osteoporosis (47 to 87 years old, average of 68.3 ± 8.2 years old) (10,11) and 513 never treated for osteoporosis (41 to 87 years old, average of 65.8 ± 7.4 years old) (9,11).…”
Section: Methodsmentioning
confidence: 99%
“…The present crosssectional study used the baseline data from all these women as they entered the study protocols, which were conducted by the same professionals and utilized the same methodology for measurement of antrhopometric and body composition parameteres. The selection criteria for choosing study participants are described in details in the publications resulting from these three studies (9)(10)(11). For further analysis, these women were divided into two groups: 430 that were undergoing treatment for osteoporosis (47 to 87 years old, average of 68.3 ± 8.2 years old) (10,11) and 513 never treated for osteoporosis (41 to 87 years old, average of 65.8 ± 7.4 years old) (9,11).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies demonstrated that HIV positive population is more likely to have 25-OH-vitamin D deficiency in contrast to HIV negative subjects. Besides classic risk factors like reduced exposure to light, low vitamin D intake diet, female sex, high BMI, hyperparathyroidism, there may be some HIV-related factors for vitamin D levels disturbances [26,27]. The mechanism responsible for low vitamin D levels in HIV infected subjects is not clear.…”
Section: Resultsmentioning
confidence: 99%
“…The evolution of osteoporosis and associated fractures are conditioned by some risk factors [5][6][7][8][9][10] , which lead to an osteometabolic imbalance caused by the deficiency of essential nutrients to maintain active bone metabolism, with the main nutrients being calcium and vitamin D 7,11,12 .…”
Section: Introductionmentioning
confidence: 99%